School librarians supporting students' reading for pleasure: A job description analysis. Issue 2 (August 2021) - Merga, Margaret K; Ferguson, Catherine
Reading for pleasure is an undervalued but highly beneficial practice conferring a range of educative and socio-emotional advantages. School librarians may play a key role in supporting reading for pleasure and associated literature advocacy; however, relatively little is known about how reading for pleasure may be valued within the job description of contemporary school librarians. It cannot be assumed that reading for pleasure is positioned as a valued aspect of the school librarians' educative role in the United States and Australia, given factors such as evolving demands placed on the profession. Through hybrid content analysis of job description documents, this article explores which aspects of the current school librarian role are related to supporting reading for pleasure, comparing expectations between nations. While there are some similarities in the nature of the reading for pleasure role in the United States and Australia, Australian school librarians are far more likely to be expected to foster reading for pleasure.